Estudiantes de la Extensión de San Miguel, visitaron las instalaciones de la Facultad de Ciencias de la Salud y del Ser Humano. - Llivi Ruilova, Danny Vicente (2023)
Leveling students from the San Miguel Extension, visited the facilities of the Faculty of Health and Human Sciences, located on the Dr. Gabriel Galarza López Campus; to know the equipment and academic offer;